`New' lists for `old': (Re-)constructing the poor in the BPL census - Roy, Indrajit (2011)
This paper aims to understand the implications of implementing the Saxena Committee's recommendations in respect of identifying the poor in India. Relative to the one currently in use, the application of the proposed methodology appears to be more beneficial in general to social groups such as scheduled tribes, most backward classes and mahadalits, as well as those landowning households that might suffer from specific debilitating conditions. However, in some cases it is less sensitive to Muslims, non-mahadalit scheduled castes and agricultural labourers. These observations are based on the results of a census survey covering 4,500 households in 18 rural wards of Bihar and West Bengal. By comparing the subset of households classified as poor according to the 2002 and the 2009 methodologies, the paper analyses "moving in" and "moving out" of poverty lists according to occupational categories, caste groups and landowning profile of the poor. - Reproduced.
Keywords: Poverty